Manajemen Pembiayaan Dalam Meningkatkan Pelayanan Prima (Excellent Service) - Aspupaten Aspupaten (Pedir Research Institute, 2021)
Abstract: The purpose of this article is to describe the planning, implementation, and supervision of education financing at MI Khoirul Anam Menganti Gresik. This research is a qualitative research with a case study approach. From the results of data analysis, research findings were obtained as follows: 1) Planning in the form of budget efficiency maximizing management functions and accommodated student needs. 1) The implementation of education financing as the process of implementing education financing involves the implementer acting according to the plan with the BOS technical instructions, the importance of orientation and moving operators so that the vision is achieved by prioritizing the actuating and prudence principles. 3) Educational financing supervision (controlling) has the function of monitoring all activities in the use of education budget financing, preventing errors, and preventing deviations. in fact there is still financing that is not listed in the APBM, so additional costs are needed from other sources managed by MI Khoirul Anam.